The Influence of Institutional Factors on the Value Relevance of Accounting Information: Evidence from Jordan - Jabar, Dhia Shamki (2012)
The purpose of the study was to present empirical evidence on the value relevance of accounting information in Jordan; whether institutional factors influence this value relevance and to determine which share price proxy is more reliable in indicating value relevance. The study examines the influence of institutional factors (foreign ownership, trading volume, financial disclosure time, financial disclosure level, number of shareholders, listing status, company’s age and type of industry) on the value relevance of accounting information (earnings, book value and cash flows relative to three share price proxies including average annual share price, annual closing share price and share price after a three-month period following the financial year-end) for Jordanian services and industrial companies during the period from 2004-2009. The study found that book value has the greatest value relevance and the best predictor for firm value. The value relevance of earnings and book value is greater for companies having foreign ownership, larger trading volume, larger shareholder numbers that conform to financial disclosure time, that are listed on the main board and that are older in age. Value relevance of book value is greater for companies complying with disclosure requirements and for services companies. Finally, annual closing share price proxy is more reliable in detecting the value relevance of accounting information. The findings suggest that market participants might be able to extract the firm value through the aforementioned institutional factors. The study extends the valuation model by including cash flows together with earnings and book value. The findings demonstrate that there is a shift away from earnings towards book value as the basis of firm valuation.